The C4.5 Algorithm in Data Mining for Classifying Prospective Student Admissions (A Case Study of AMIK-DP) - Rezki Fauzi; Gustri Efendi; Fitriany Fitriany (The Future of Education Journal, 2026)
Algorithm c4.5 data classification algorithm bertipe decision tree. algorithm decision tree c4.5 built with a few stage that cover attribute election as root, make branch to every value and divide case in branch. tahap-tahan this be repeatinged to every branch until all cases in has class same. From decision tree completion so be got several rule a case. in this case author clasify pass from a student university at one particular college (AMIK Depati Parbo Kerinci) not only based on accomplishment index criteria komulatif but also extracurrucular skill likes practice labor, campus organization, assistant labor and age also be somebody yardstick to acceptable at a private resort / government. with algorithm applications c4.5 this can help side baak in recommend student university genuinely skilled.